Mechanical Properties and Microstructural Aspects of Two High-Manganese Steels with Twip/Trip Effects: A Comparative Study - Monsalve-Gonzalez, A; Artigas-Abuin, A; Bordone, M (Multidisciplinary Digital Publishing Institute (MDPI), 2021)
This article is focused on the mechanical behavior and its relationship with the microstruc-tural changes observed in two high-manganese steels presenting twinning-induced plasticity (TWIP) and transformation-induced plasticity (TRIP), namely Steel B and Steel C, respectively. Chemical compositions were similar in manganese, but carbon content of Steel B approximately doubles Steel C, which directly impacted on the stacking fault energy (SFE), microstructure and mechanical response of each alloy. Characterization of as-cast condition by optical microscope revealed a fully austenitic microstructure in Steel B and a mixed microstructure in Steel C consisting of austenite grains and thermal-induced (εt ) martensite platelets. Same phases were observed after the thermo-mechanical treatment and tensile tests, corroborated by means of X-Ray Diffraction (XRD), which confirms no phase transformation in Steel B and TRIP effect in Steel C, due to the strain-induced γFCC→εHCP transformation that results in an increase in the ε-martensite volume fraction. Higher values of ultimate tensile strength, yield stress, ductility and impact toughness were obtained for Steel B. Significant microstructural changes were revealed in tensile specimens as a consequence of the operating hardening mechanisms. Scanning Electron Microscopy (SEM) observations on the tensile and impact test specimens showed differences in fracture micro-mechanisms. © 2020 by the authors. Licensee MDPI, Basel, Switzerland.